Interaction of mental comorbidity and physical multimorbidity predicts length-of-stay in medical inpatients - Stahl-Toyota, Sophia; Nikendei, Christoph; Nagy, Ede; Bönsel, Stefan; Dönnhoff, Ivo; Unger, Inga; Szendrödi, Julia; Frey, Norbert; Michl, Patrick; Müller-Tidow, Carsten; Jäger, Dirk; Friederich, Hans-Christoph; et al. (PLOS ONE, 2023)
Background: Mental comorbidities of physically ill patients lead to higher morbidity, mortality, health-care utilization and costs. Objective: The aim of the study was to investigate the impact of mental comorbidity and physical multimorbidity on the length-of-stay in medical inpatients at a maximum-care university hospital. Design The study follows a retrospective, quantitative cross-sectional analysis approach to investigate mental comorbidity and physical multimorbidity in internal medicine patients. Patients: The study comprised a total of n = 28.553 inpatients treated in 2017, 2018 and 2019 at a German Medical University Hospital. Main measures Inpatients with a mental comorbidity showed a median length-of-stay of eight days that was two days longer compared to inpatients without a mental comorbidity. Neurotic and somatoform disorders (ICD-10 F4), behavioral syndromes (F5) and organic disorders (F0) were leading with respect to length-of-stay, followed by affective disorders (F3), schizophrenia and delusional disorders (F2), and substance use (F1), all above the sample mean length-of-stay. The impact of mental comorbidity on length-of-stay was greatest for middle-aged patients. Mental comorbidity and Elixhauser score as a measure for physical multimorbidity showed a significant interaction effect indicating that the impact of mental comorbidity on length-of-stay was greater in patients with higher Elixhauser scores. Conclusions: The findings provide new insights in medical inpatients how mental comorbidity and physical multimorbidity interact with respect to length-of-stay. Mental comorbidity had a large effect on length-of-stay, especially in patients with high levels of physical multimorbidity. Thus, there is an urgent need for new service models to especially care for multimorbid inpatients with mental comorbidity.
Veröffentlicht: 22. Juni 2023
Gesehen am 18.08.2023